Effect of electrostatic interactions in the separation of magnetite and silica using enhanced gravity concentration - Baladad, Karlo Leandro D. (Philippine Engineering Journal, 2022)
Access online through this link: https://journals.upd.edu.ph/index.php/pej/article/view/8902/7828